Influence of Unburned Carbon on Environmental-Technical Behaviour of Coal Fly Ash Fired Clay Bricks - Juan Dacuba; Eva Cifrian; Maximina Romero; Tamara Llano; Ana Andrés (Applied Sciences, 2022)
The incorporation of coal fly ash (CFA) in fired clay bricks (FCBs), as a clay replacement, contributes toward cleaner production practices. CFA disposal is an important issue worldwide due to its huge volume and to its potential negative environmental impacts, and currently does not have a recovery route due to its high concentration in unburned materials. In this study, the impact of the incorporation of two CFA, with different content of unburned carbon, FAA (low LOI) and FAB (high LOI) in FCBs, from a technical and environmental point of view was conducted. Unburned carbon plays an important role on the final properties of FCBs. The thermal decomposition during the firing process promotes an increase of water absorption, decreasing the flexural strength as the porosity increases, although the technical and mechanical properties of samples containing up to 30% FAA and percentages of 20% FAB are acceptable. The leaching behaviour showed an immobilisation of Cr and Se in FCBs while Mo reduced its mobility to values below non-hazardous limits. Acid gas emission values do not exceed the reference emission value, except for SO2 emissions while the level of CO2 emissions must be estimated based on the total annual production of the ceramic factory.